Near-infrared dye IRDye800CW-NHS coupled to Trastuzumab for near-infrared II fluorescence imaging in tumor xenograft models of HER-2-positive breast cancer - Xiao, Junhui; Qiu, Siqi; Ma, Qiufeng; Bai, Silan; Guo, Xinrong; Wang, Lishi (Journal of materials chemistry. B, Materials for biology and medicine, 2023)
Near-infrared II fluorescent probes targeting tumors for diagnostic purposes have received much attention in recent years. In this study, a fluorescent probe for the NIR-II was constructed by using IRDye800CW-NHS fluorescent dye with Trastuzumab, which was investigated for its ability to target HER-2-positive breast cancer in xenograft mice models. This probe was compared with Trastuzumab-ICG which was synthesized using a similar structure, ICG-NHS. The results demonstrated that the IRDye800CW-NHS had significantly stronger fluorescence in the NIR-I and NIR-II than ICG-NHS in the aqueous phase. And the different metabolic modes of IRDye800CW-NHS and ICG-NHS were revealed in bioimaging experiments. IRDye800CW-NHS was mainly metabolised by the kidneys, while ICG-NHS was mainly metabolised by the liver. After coupling with Trastuzumab, Trastuzumab-800CW (TMR = 5.35 ± 0.39) not only had a stronger tumor targeting ability than Trastuzumab-ICG (TMR = 4.42 ± 0.10) based on the calculated maximum tumor muscle ratio (TMR), but also had a comparatively lower hepatic uptake and faster metabolism. Histopathology analysis proved that both fluorescent probes were non-toxic to various organ tissues. These results reveal the excellent optical properties of IRDye800CW-NHS, and the great potential of coupling with antibodies to develop fluorescent probes that will hopefully be applied to intraoperative breast cancer navigation in humans. The NIR-II fluorescent probe Trastuzumab-800CW was used for NIR-II fluorescent targeting of HER-2-positive breast cancer tumors and was systematically compared with Trastuzumab-ICG.